Transformasi Pendidikan: Peran Strategis Kepala Sekolah dalam Membangun Peserta Didik Berkualitas - Triana Dewi; Abidin, Upik Khoriul (Tahta Media Group, 2023)
This article aims to find out the strategy and implementation of the principal's leadership to build students with quality and Islamic character, which is carried out at MI Muhammadiyah 12 Ngampel, Balong, Ponorogo. As the person in charge of educational institutions, the madrasah principal is a leader in education with significant influence and responsibility on the growth of madrasah institutions. In line with this, the role of the madrasah head will have a significant impact on the progress and development of education, with the aim of improving standards and human resources in the quality of education itself. There are several strategies of the principal of MI Muhammadiyah 12 Ngampel in shaping students, namely (1) being a role model for students; (2) Doing dhuha prayers and dhuhur prayers in congregation, Tahfidz, and BTA every day; (3) implementing honesty, this is something that will be very fundemental and very important in the formation of good character for students in accordance with the guidance of Islamic teachings; (4) The development of manners and responsibilities related to behaviour, morals and values in interpersonal interactions as well as in the context of class and society. This research is a field research with a qualitative approach. By collecting data through interviews, surveys, observations and documentation. This research uses qualitative methods to capture and translate phenomena and facts related to the leadership of the principal of MI Muhammadiyah 12 Ngampel.